KIMYODAN NAZARIY BILIMLAR VA AMALIY KOʻNIKMALARNI SHAKLLANTIRISHDA TURLI MANTIQIY YONDASHUVLARDAN FOYDALANISH - Kuchkarov, Mexriddin (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This article analyzes the possibilities of forming theoretical knowledge and practical skills in chemical education. It pays special attention to inductive and deductive approaches in chemical education. The increase in the effectiveness of training as a result of the use of various logical approaches to the organization of laboratory experiments, demonstration experiments and practical exercises is justified.